2021
DOI: 10.21580/pjpp.v6i1.6857
|View full text |Cite
|
Sign up to set email alerts
|

How do they deal with the Pandemic? The effect of secure attachment and mindfulness on adolescent resilience

Abstract: Building resilience is a great necessity, especially for adolescents who have spent most of their time at home with their families and have also had to cope with the pandemic situation. Resilience ensures that they persevere, adapt, and rise to the occasion when dealing with difficult circumstances. This study aims to empirically test the role of secure attachment and mindfulness in adolescent resilience in the New Normal era. The subjects were 220 adolescents, students at junior high school in the city of Sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
2
Order By: Relevance
“…Menurut Reivich & Shatte dalam Aini et al (2021), faktor-faktor kunci dari resiliensi adalah mindset individu, sikap positif individu ketika menghadapi kesulitan, pendorong/keinginan untuk bangkit, gaya berpikir, dan keyakinan individu dalam menghadapi kesulitan sebagai hal yang positif. Sedangkan menurut Kumpfer (2005) f. Outcomes (luaran) yang positif atau adaptasi yang berhasil.…”
Section: Faktor Yang Berpengaruh Terhadap Resiliensiunclassified
See 1 more Smart Citation
“…Menurut Reivich & Shatte dalam Aini et al (2021), faktor-faktor kunci dari resiliensi adalah mindset individu, sikap positif individu ketika menghadapi kesulitan, pendorong/keinginan untuk bangkit, gaya berpikir, dan keyakinan individu dalam menghadapi kesulitan sebagai hal yang positif. Sedangkan menurut Kumpfer (2005) f. Outcomes (luaran) yang positif atau adaptasi yang berhasil.…”
Section: Faktor Yang Berpengaruh Terhadap Resiliensiunclassified
“…Individu yang memiliki mindfulness dan safe attachment akan mampu untuk mencoba menggunakan kesadaran mereka dan berfokus pada mengatasi masalah. Remaja yang memiliki mindfulness tinggi akan berusaha untuk memiliki kualitas hidup yang baik dan mampu untuk bangkit dari kesulitan yang dihadapi (Aini et al, 2021).…”
Section: Upaya Meningkatkan Resiliensi Pada Remajaunclassified
“…Mindfulness has been found to have positive effects on adolescents, such as reducing the symptoms of mental health problems, reducing negative behaviors, and increasing resiliency (Aini et al, 2021;Carsley et al, 2018;Dunning et al, 2018;Franco et al, 2016;Vanzin et al, 2020). Salmoirago-Blotcher et al (2019) even found that mindfulness could successfully reduce impulsivity in adolescents after they had received mindfulness training.…”
Section: Mindful Individuals Have Full Awareness Of Eventsmentioning
confidence: 99%
“…On the role of secure attachment and mindfulness in adolescent resilience in the new normal era indicate a significant and positive relationship between secure attachment, mindfulness, and adolescent resilience in the new normal era. Attachment plays an important role in helping individuals fulfill developmental tasks in their lives, which will shape a person to become resilient or enable them to face problems and difficulties in their lives [13]. From the above explanation, it can be concluded that self-esteem and attachment play important roles in helping individuals fulfill developmental tasks in their lives, which will shape a person to become resilient or enable them to face problems and difficulties in their lives.…”
Section: Introductionmentioning
confidence: 96%